Correction of facial skin aging signs using exosomes - T.N. Korolkova; I.A. Shepilova; T.G. Dovbeshko (Russian Journal of Clinical Dermatology and Venereology, 2026)
Background. Skin aging is a multifactorial process caused by internal mechanisms and external influences. Gradual changes in the epidermis and dermis lead to impaired skin functions. Restoring these functions is an important task. Objective. Evaluation of the results of using a two-component complex with exosomes in patients with signs of facial skin aging. Material and methods. During this study, 22 patients (mean age 53.1±1.3 years) with Fitzpatrick skin phototypes I-III, wrinkles and other signs of facial aging were observed. The patients underwent 4 microneedling procedures followed by application of a two-component complex with an interval of 7±4 days between visits. A control examination was performed before each procedure, 1 week and 5 months after the course of procedures. The examination included an objective assessment by a doctor, a subjective assessment by the patient (questionnaire survey), photography, corneometry, mexametry, measurement of transepidermal water loss, and elastometry. Appropriate methods were used for statistical processing. Results. The used products do not disrupt the skin’s barrier properties. After 6 months from the start of therapy, skin extensibility (R0) decreased by 5—11%, and its return (R1, R8) to the initial state improved by 4—12%, as did the degree of fatigue (R3, R4, R9) by 3—17%. The elasticity of the forehead skin (R6) increased by 25%. The elasticity (R2, R5, R7) of the cheek skin increased by 5—6%. The overall elasticity indicators (F0, F1) improved by 13—18%. The patient’s subjective assessment of the skin condition and the doctor’s objective assessment were consistent, indicating a reduction in external signs of aging. Conclusion. The use of the two-component complex with exosomes after microneedling reduces the signs of facial skin aging. The procedures do not disrupt the skin barrier properties, are well tolerated, and do not cause allergic reactions.